Activation and Regulation of B Cell Responses by Invariant Natural Killer T Cells - Doherty, Derek G.; Melo, Ashanty M.; Moreno-Olivera, Ana; Solomos, Andreas C. (Frontiers in Immunology, 2018)
CD1d-restricted invariant natural killer T (iNKT) cells play central roles in the activation and regulation of innate and adaptive immunity. Cytokine-mediated and CD1d-dependent interactions between iNKT cells and myeloid and lymphoid cells enable iNKT cells to contribute to the activation of multiple cell types, with important impacts on host immunity to infection and tumors and on the prevention of autoimmunity. Here we review the mechanisms by which iNKT cells contribute to B cell maturation, antibody and cytokine production, and antigen presentation. Cognate interactions with B cells contribute to the rapid production of antibodies directed against conserved non-protein antigens resulting in rapid but short-lived innate humoral immunity. iNKT cells can also provide non-cognate help for the generation of antibodies directed against protein antigens, by promoting the activation of follicular helper T cells, resulting in long-lasting adaptive humoral immunity and B cell memory. iNKT cells can also regulate humoral immunity by promoting the development of autoreactive B cells into regulatory B cells. Depletions and functional impairments of iNKT cells are found in patients with infectious, autoimmune and malignant diseases associated with altered B cell function and in murine models of these conditions. The adjuvant and regulatory activities that iNKT cells have for B cells makes them attractive therapeutic targets for these diseases.